Adaptive servo ventilation for central sleep apnoea in heart failure: SERVE-HF on-treatment analysis. Issue 2 (31st August 2017) - Woehrle, Holger; Cowie, Martin R.; Eulenburg, Christine; Suling, Anna; Angermann, Christiane; d'Ortho, Marie-Pia; Erdmann, Erland; Levy, Patrick; Simonds, Anita K.; Somers, Virend K.; Zannad, Faiez; Teschler, Helmut; et al.
This on-treatment analysis was conducted to facilitate understanding of mechanisms underlying the increased risk of all-cause and cardiovascular mortality in heart failure patients with reduced ejection fraction and predominant central sleep apnoea randomised to adaptive servo ventilation versus the control group in the SERVE-HF trial. Time-dependent on-treatment analyses were conducted (unadjusted and adjusted for predictive covariates). A comprehensive, time-dependent model was developed to correct for asymmetric selection effects (to minimise bias). The comprehensive model showed increased cardiovascular death hazard ratios during adaptive servo ventilation usage periods, slightly lower than those in the SERVE-HF intention-to-treat analysis. Self-selection bias was evident. Patients randomised to adaptive servo ventilation who crossed over to the control group were at higher risk of cardiovascular death than controls, while control patients with crossover to adaptive servo ventilation showed a trend towards lower risk of cardiovascular death than patients randomised to adaptive servo ventilation. Cardiovascular risk did not increase as nightly adaptive servo ventilation usage increased. On-treatment analysis showed similar results to the SERVE-HF intention-to-treat analysis, with an increased risk of cardiovascular death in heart failure with reduced ejection fraction patients with predominant central sleep apnoea treated with adaptive servo ventilation. Bias is inevitable and needs to be taken into account in any kind of on-treatment analysis in positive airway pressure studies. SERVE-HF on-treatment results showed increased cardiovascular risk similar to the intention-to-treat analysis http://ow.ly/hoO130dx4s9